A comprehensive review on the integration of advanced oxidation processes with biodegradation for the treatment of textile wastewater containing azo dyes - Chaturvedi A.; Rai B.N.; Singh R.S.; Jaiswal R.P. (My University, 2025)
The threat of dye contamination has achieved an unsurpassed abnormal state lately due to their massive consumption in several enterprises including textile, leather, cosmetic, plastic, and paper industries. This review focuses on the integrations of various advanced oxidation processes (AOPs), such as Fenton, photocatalysis, and ozonation, with biodegradation for the treatment of textile azo dyes. Such integrations have been explored lately by researchers to bring down the processing cost and improve the degree of mineralization of the treated dyeing wastewater. The review refers to the basic mechanisms, the influence of various process parameters, outcomes of recent works, and future research directions. All the three AOPs, independently, demonstrated substantial color reduction of 54-100%. The ozonation process, stand-alone, showed the most efficient decolorization (of 88-100%) consistently in all reviewed research works. In contrast, all three AOPs independently offered varied and inadequate COD reduction in the range of 16-80%. The AOPs, after getting integrated with biodegradation, yielded an additional reduction (of 11-70%) in the COD-levels and (of 16-80%) in the TOC-levels. Further, the integration of AOPs with biodegradation has potential to significantly reduce the treatment costs. The review suggests further research efforts in the direction of sequencing chemical and biological routes such that their synergistic utilization yield complete detoxification of the textile azo dyes economically at large-scale. © 2020 Walter de Gruyter GmbH, Berlin/Boston.